Executive decision - Baird, Stuart (Philipphines : Warner Home Video.)
Looking for excitement? You've made the right decision! Producer Joel Silver adds to his string of hits and Stuart Baird, editor of Silver's Lethal Weapon and other action spectaculars, makes a memorable directional debut on a movie "faster than Speed and more fun than Broken arrow" (Allen Barra, Newhouse Newspapers). Kurt Russell, Steven Seagal, Halle Berry, John Leguizamo and others in a heroic ensemble are on board for first-class thrills. The mission: board a hijacked 747 in midair. Avoid detection. Locate and disable a hair-triggered nerve-toxin bomb that could wipe out the U.S. Eastern Seaboard. Execute a split-second attack that overwhelms the terrorists and safeguards the passengers. Do it all without air-to-ground radio. And do it before an increasingly jittery U.S. military blasts the airliner out of the sky. "I hope there's a good movie on this flight," an anti-terrorists operative quips. As it turns out, there's a great one: Executive Decision!